FRACTIONATION OF SULFUR ISOTOPES IN THE BISULFITE ADDITION REACTION - Sheppard, William Arthur (My University, 1951)
The equilibrium constants for the isotopic exchange of S32 and S34 have boon measured for the equilibrium reaction of bisulfite ion with eight different carbonyl compounds. This was accomplished by comparing the mass spectrometric measurements of the S32/S34 abundance ratios of the reacting bisulfite ion and the addition compound. The S34 was found to concentrate to the extent of 1-2% in the addition compound. These equilibrium constants have boon put to a unique use to confirm that the addition com- pound has a carbon-sulfur bond structure rather then a carbon- oxygen-sulfur structure. An attempt has been made to measure the isotope effect in. the formation of the carbon-sulfur bond under conditions which favour an unidirectional process. The effect appeared to be zero. f It is proposed that the initial product of the reaction has the carbon-oxygen-sulfur structure and that this compound is thon rapidly converted to the more stable carbon-sulfur bond form, fractionation of the sulfur isotopes occurring in the latter process only.
Keywords: Chemistry